Changing Identity Through Material Culture: Folklore, the Fur Trade, and the Internet - Call, Hadyn (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
Abstract Many humans, at some point, have the desire to become something or someone they are not. Across the globe, groups of people who want to relive the past form re-enacting communities to engage in living history. The method by which these people change their identity is through a historically based material culture, disseminated in great part by the Internet. This article focuses on those who re-enact the lifestyle of the trappers of the Rocky Mountain fur trade, specifically examining a prestigious group called the American Mountain Men, and demonstrates how folklore is spread through material culture both physically and intangibly.